A Digital System Model for Online Driver's License for Department of Land Transport in Thai Supply Chain - Artaphon Chansamut (International Journal of Supply Chain Management, 2023)
The purpose of paper study were to study  a digital system model for online driver’s license department of land transport in Thai supply chain and  evaluation of the model  . The sample group in this study consisted of ten experts using purposive sampling. Data were analysed by arithmetic mean and standard deviation. The research findings model six elements namely main components, Supplier, Department of land transport, Finished person ,Customers satisfaction and Return. The ten experts agree that a digital system model for online driver’s license department of land transport in Thai supply chain was high suitability which mean that The model may be appropriately applied in actual work settings.